Emerging Trends in E-Commerce and Barriers in Current Scenario in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
E-Commerce or electronic trade comprises basically of the exchange of goods, purchasing, offering, promoting, publicizing and adjusting of products or services with the assistance of web based systems. The introduction of organizations, for example, eBay and Amazon truly started to lead the path in E-business. Presently a day's E-business organizations assume most critical part in world trade. The E-commerce part has seen enormous development. The development was driven by fast innovation reception driven by the expanding utilization of gadgets, for example, modern system, mobiles, access to the web through broadband, 3G, 4G and validity of E-commerce organizations and so on, which prompted an expanded online customer base. This paper depicts the emerging trends in e-commerce and barriers in current scenario in India